Utilization of cuttle fish (Sepia officialis) bone meal as calcium supplement in the diet of pigs - Mercy, A D; Bindhu, K B; Shyama, K (The Indian Journal of Animal Sciences, 2011)
The effect ofutilization ofcuttle fish bone-meal as calcium supplement on growth performance was studied in 40 weaned Large White Yorkshire piglets. Four dietary treatments, T1 (control diet with 9% dried fish and 1%mineral mixture), T, (dicalcium phosphate), T3 (50% of di-calcium phosphate of T’l was replaced by cuttle fish bone and diammonium phosphate) and T4 (in which dicalcium phosphate was replaced fully with cuttIe fish bone and diammonium phosphate) were formulated and given to the 4 groups. Total body weight gain and feed efficiency of pigs maintained on T4 was better than that of T1 and T3 (P<0.01)Cost of feed per kilogram gain was also lower for T4 (p<.01)compared to that of other 3 groups, indicating that euttle fish bone can be used economically as a source of calcium along with diammonium phosphate as phosphorus source.